Correlation Between Community Image Of Madrassa With Professionalism Of English Teachers And Student Learning Achievement - Sholeh, Moch (Journal of World Science, 2022)
Effective education is the occurrence of the teaching and learning process by fulfilling the main elements, namely teachers, students, and madrasahs or schools, where the teaching and learning process and other supporting infrastructure facilities such as community support, especially parents of students, to get a good image of the community. The effectiveness of the teaching and learning process will greatly affect the overall image of education, of course. The purpose of this research is to describe the professionalism of teachers and the English language skills of students 2. Depicting the image of the community against the image of Madrasah 3. To prove the correlation between teacher professionalism and students' English language skills with The Community Image of madrasah image Tsanawiyah Arjawinangun. This research was conducted using quantitative methods with a statistical approach through the SPSS 11.5 program, with the following stages: determination of the location and time of the study, data collection through observation, interviews, and documentation studies, determining data sources with several informants related to research problems, as well as conducting data analysis on the existence of a correlation between variable-variables studied. The results of the study found the following findings: 1. The professionalism of English teachers and student learning achievement in MTs Negeri Arjawinangun is quite good. 2. Public image of MTs N Arjawinangun image is good with indicators of the number of people who register their daughter's son to MTs Negeri Arjawinangun and 3. Correlation between Community Image of Madrasah image with Teacher Professionalism and Student English Learning Achievement by 0.72. This means that the correlation value above shows that there is a positive correlation between the professionalism of English language teachers and students' learning achievements to the public image of madrassa imagery